Acute skeletal muscle responses to very low‐load resistance exercise with and without the application of blood flow restriction in the upper body. (2nd December 2018) - Buckner, Samuel L.; Jessee, Matthew B.; Dankel, Scott J.; Mattocks, Kevin T.; Mouser, J. Grant; Bell, Zachary W.; Abe, Takashi; Loenneke, Jeremy P.
Summary: The purpose was to examine the acute skeletal muscle response to high load exercise and low‐load exercise with and without different levels of applied pressure (BFR). A total of 22 participants completed the following four conditions: elbow flexion exercise to failure using a traditional high load [70% 1RM, (7000)], low load [15% 1RM, (1500)], low load with moderate BFR [15%1RM+40%BFR(1540)] or low load with greater BFR [15% 1RM+80%BFR(1580)]. Torque and muscle thickness were measured prior to, immediately post, and 15 min postexercise. Muscle electromyography (EMG) amplitude was measured throughout. Immediately following exercise, the 7000 condition had lower muscle thickness [4·2(1·0)cm] compared to the 1500 [4·4 (1·1)cm], 1540 [4·4(1·1)cm] and 1580 [4·5(1·0)cm] conditions. This continued 15 min post. Immediately following exercise, torque was lower in the 1500 [31·8 (20) Nm], 1540 [28·3(16·9) Nm, P <0·001] and 1580 [29·5 (17) Nm] conditions compared to the 7000 condition [40 (19) Nm]. Fifteen minutes post, 1500 and 1540 conditions demonstrated lower torque compared to the 7000 condition. For the last three repetitions percentage EMG was greater in the 7000 compared to the 1580 condition. Very low‐load exercise (with or without BFR) appears to result in greater acute muscle swelling and greater muscular fatigue compared to high load exercise.